Lei Muwaji: dos discursos do enfrentamento aos diálogos do reconhecimento - SÁ JUNIOR, Adalberto Fernandes (Universidade Federal do Pará, 2017)
This dissertation analyses the constitutionality of the legal project nº 1.057/2007, mostly known as Muwaji Law, that deals with, according to its text, the struggle against indigenous peoples’ traditional customs that are “harmful” to the human rights of children. We concluded that this project is unconstitutional for disrespecting the self-determination right of these peoples. First, it undermines the equality principle, the right to non-discrimination and the mutual recognition convention. The indigenous minorities are treated in a discriminatory manner. Secondly, the fairness principle, the self-government right and the convention of consent are not respected. Indigenous peoples did not participate in due processes of political deliberation. Finally, the integrity principle, the right to cultural integrity and the convention of continuity are not taken into account. The Amerindian perspectives on childhood are not respected. As a method, we use the theory of law as integrity by Ronald Dworkin.